PROBLEMATIKA KIPRAH DEWAN PENGAWAS SYARI’AH DPS DI PERBANKAN SYARI’AH - Fitra Nelli (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2015)
Abstract Sharia Banking Act is the crystallization of the long struggle of the Muslims of Indonesia in implementing the principles of Shari'ah in muamalah, especially muamalah maliyah. Realization of Shariah principles in Shariah banking system should refer to the three fundamental principles, namely: 1) the principle of fairness, 2) avoid activities that are prohibited shari'ah, and 3) the aspect of expediency. That the principles of the Shari'ah can be realized well in Sharia banking, then there must be control by the Shariah Supervisory Board (DPS). Shariah Supervisory Board (DPS) is an independent body that was placed by the National Sharia Council (DSN) on the banking and financial institutions Shari'ah. Gait Sharia Banking Council (DPS) in the realization of the principles of Shari'ah in Shariah banking can be seen from the role and functions of the Shariah Supervisory Board in Sharia banking, which provide guidance, ideas, suggestions and advice to directors Islamic banks on matters pertaining to sharia aspects and examine, inspect, examine and assess the implementation of the operational DSN fatwa on Islamic banks. Kata kunci : Kiprah, Dewan Pengawas Syari’ah, Bank Syari’ah.